1998
DOI: 10.1136/jmg.35.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Alport syndrome, mental retardation, midface hypoplasia, and elliptocytosis: a new X linked contiguous gene deletion syndrome?

Abstract: (JMed Genet 1998;35:273-278)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 33 publications
3
41
1
Order By: Relevance
“…For example, facial features of the patient (Fig. 1A) appear to have similarity with previously reported patients with ATS-MR (Jonsson et al, 1998;Meloni et al, 2002a). The ATS-MR patients have normal intrauterine and postnatal growth, including head circumference, (extra) hair whorls, downslanting palpebral fissures, midface hypoplasia, flat nasal bridge, periorbital fullness, facial hypotonia, and persistent fingertip fetal pads (Meloni et al, 2002a).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…For example, facial features of the patient (Fig. 1A) appear to have similarity with previously reported patients with ATS-MR (Jonsson et al, 1998;Meloni et al, 2002a). The ATS-MR patients have normal intrauterine and postnatal growth, including head circumference, (extra) hair whorls, downslanting palpebral fissures, midface hypoplasia, flat nasal bridge, periorbital fullness, facial hypotonia, and persistent fingertip fetal pads (Meloni et al, 2002a).…”
Section: Discussionsupporting
confidence: 50%
“…Several patients with the Alport syndrome-mental retardation contiguous gene deletion syndrome (ATS-MR) have been reported (Robson et al, 1994;Jonsson et al, 1998;Piccini et al, 1999;Meloni et al, 2002a). The interstitial deletion at Xq22.3 in the patient is entirely contained in the deletion region described earlier for the ATS-MR.…”
Section: Discussionmentioning
confidence: 95%
“…We have previously reported that family 1 has a COL4A5 gene deletion 10 extending beyond the gene towards the telomere 12 (AMME, OMIM 300194). In order to find additional patients with a deletion in Xq22.3, we carefully examined previous publications and found two interesting reports in which nephropathy was associated with deafness and mental retardation.…”
Section: Patientsmentioning
confidence: 99%
“…In 1998, we described a new Xq22.3 contiguous gene syndrome which we named AMME (OMIM 300194) because of the distinctive features observed in affected males: Alport syndrome (A), mental retardation (M), midface hypoplasia (M), and elliptocytosis (E). 10 After the original publication, clinical re-evaluation of the family showed alterations of cardiac rhythm and morphology on echocardiography. 11 To elucidate the molecular basis of this complex syndrome, we cloned three genes from the deleted region: FACL4, 12 AMMECR1, 13 and KCNE1L, 11 recently renamed KCNE5.…”
mentioning
confidence: 99%
“…Recently we reported a family in which affected males have typical features of X-linked Alport syndrome (hematuria and hearing loss), but in addition they have mental retardation, facial and digital dysmorphology, and elliptocytosis (9). The most distinctive facial feature was midface hypoplasia, and the features did not resemble those found in any other reported X-linked mental retardation condition.…”
mentioning
confidence: 74%